Unmasking the unexpected: a rare case report of B-acute lymphoblastic leukemia - Ahuja, Jyoti; Arora, Vivek (International Journal of Contemporary Pediatrics, 2026)
Acute lymphoblastic leukemia (ALL) is a neoplastic proliferation of immature hematopoietic cells, commonly presenting with anaemia, thrombocytopenia, neutropenia, or hepatosplenomegaly. Paraplegia as the initial manifestation is extremely rare. We report a 6-year-old girl presenting with backache and sudden paraplegia. MRI revealed a thoracic epidural mass (D1-D6). Tumor excision and laminectomy were performed, and histopathology confirmed B-cell ALL. This case highlights the importance of considering leukemia in children with acute spinal cord compression.